Biomimetic, bioresponsive, and bioactive materials an introduction to integrating materials with tissues - Santin, Matteo; Phillips, Gary (Gary J.) (Wiley, 2012)
This comprehensive introduction to biomaterials discusses how materials are selected, designed, and modified for integration with living tissue. Biomaterials have applications in tissue engineering, medical devices, orthopedics, and other areas.